PERLINDUNGAN LINGKUNGAN HIDUP DI SEKTOR PERTANIAN MELALUI PENGEMBANGAN WISATA AGRO - Made Kembar Sri Budhi (Environmental Research Center (PPLH) of Udayana University, 2010)
The goal of research was to study alternative ways in order to increase farmersíncome, environment saving efforts in the agricultural sector, diversification of products and also to offer tourist destination. These Objectives are very important since the interest of people on agricultural economical efforts have being reduced, especially the young generation to pursue agricultural business which is inherited from generation to generation. In addition to maintain environmental quality, especially the agricultural sector which grew more and more switching functions, and to provide an alternative model of farming that has to do with tourism businesses to avoid saturation due to recent tourist products related to the needs of nature become a priorities. The results of the study showed that based on the potential relevant models, to stimulate the agricultural sector, together with efforts to maintain environmental quality, and progress associated with the tourism sector is to develop agro tourism. Many models can be developed both in the context of the open or closed nature tourism, as well as natural or artificial contexts. In order to bring in the expected goal, it is necessary to increase the quantity and quality related to human resources, infrastructure, financing and the commitment of the entire society with the government to develop agro-tourism.